Sistem Informasi Lulusan Dengan Metode Online Analitycal processing (OLAP) Pada Politeknik Negeri Kupang - Ndoloe, Lita Alfriany (Universitas Diponegoro, 2012)
The educational institution need the leadership/ decision makers are always trying to find some information / decisions that are beneficial to the students, so that when they graduate can get a job quickly. To make it easier to get the information using OLAP. The purpose of this research is to make information systems graduates by using Online Analytical Procesing (OLAP). In the modelingsystem used Context Diagram and Data Flow Diagram. Information systems graduates begins with collecting data on graduates, perform analysis with the concept of Roll Up, presents information generated OLAP and graphs. Graduate information systemsprovide information quality graduates, useful for leaders to make decisions. Graduate information systems can be applied to the State Polytechnic Department of Electronics Kupang. Results showed developmental process OLAP uptake needs graduates in public and private.Keywords: OLAP,Graduate information systems, Roll Up